2014
DOI: 10.1016/j.bpj.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Effects of Macromolecular Crowding on an Intrinsically Disordered Protein: A Small-Angle Neutron Scattering Study

Abstract: Small-angle neutron scattering was used to study the effects of macromolecular crowding by two globular proteins, i.e., bovine pancreatic trypsin inhibitor and equine metmyoglobin, on the conformational ensemble of an intrinsically disordered protein, the N protein of bacteriophage λ. The λ N protein was uniformly labeled with (2)H, and the concentrations of D2O in the samples were adjusted to match the neutron scattering contrast of the unlabeled crowding proteins, thereby masking their contribution to the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 85 publications
(124 reference statements)
6
81
0
Order By: Relevance
“…[1][2][3][4][5] It is well established that excluded-volume interactions with crowder particles can have a significant stabilizing effect on globular proteins, as demonstrated by experiments with synthetic crowding agents such as Ficoll or dextran. 6 Today, experiments are increasingly often performed under more realistic crowding conditions, using concentrated protein solutions [7][8][9][10] or cells. 9,[11][12][13][14][15][16] In these systems, it has been shown that other interactions may dominate over the steric repulsions and lead to a net destabilization of globular proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] It is well established that excluded-volume interactions with crowder particles can have a significant stabilizing effect on globular proteins, as demonstrated by experiments with synthetic crowding agents such as Ficoll or dextran. 6 Today, experiments are increasingly often performed under more realistic crowding conditions, using concentrated protein solutions [7][8][9][10] or cells. 9,[11][12][13][14][15][16] In these systems, it has been shown that other interactions may dominate over the steric repulsions and lead to a net destabilization of globular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 As crowding agent, we pick the 58-residue bovine pancreatic trypsin inhibitor (BPTI), which was used in recent experiments on the disordered N protein of bacteriophage λ. 10 We model the BPTI molecules in full atomistic detail but assume them to stay folded with restricted internal dynamics. For comparison, we also perform simulations with simple hard-sphere crowders.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological role of the COR15 proteins is to stabilize chloroplast membranes at mild freezing temperatures between approximately 25°C and 215°C, at which extracellular ice crystallization leads to partial cell dehydration and increased molecular crowding. Macromolecular crowding, applied either through high concentrations of globular proteins or of polymers such as dextran, has generally only limited effects on IDP structure (Mouillon et al, 2008;Szasz et al, 2011;Goldenberg and Argyle, 2014). However, osmolyte-induced crowding was also ineffective to induce folding in some plant LEA proteins (Mouillon et al, 2008), although it can induce refolding of denatured globular proteins (Davis-Searles et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The specific value of x c should in principle vary with the nature of interactions in the ternary system of polymer, crowding particles, solvent, and N . Nevertheless, the estimated x c is a guide to obtain an approximate estimate of φ c , and we show below [34], and λN in BPTI or metmyoglobin (Mb) [35]. To compare with experiments, we superimposed our simulation results with N = 100 and λ = 0.9, 1.9, 3.8.…”
mentioning
confidence: 99%